ELECTRON IMPACT INDUCED FRAGMENTATION OF Β-NITROAMINES - Mahasneh, Ali S. (European Scientific Journal, ESJ, 2013)
One of the most characteristic electron impact induced fragmentation processes of β-nitroamines, investigated here, is loss of nitromethane and/or nitromethylene radical to produce an imine or imonium ion. Through the comparison of an imine spectrum with that of β-nitroamine derived from, it was possible to shed additional light on the course of most significant fragmentation reaction of β-nitroamines. The other two most characteristic fragmentation processes of β-nitroamines upon electron impact are i) loss of aniline or an aniline moiety with expulsion of a nitroalkene. Similer steps are also noted in fragmentation of amines, aliphatic ethers and thioethers. ii) Fragmentation with loss of NO2 or HNO2 followed by a series of fragmentation processes yielding low m/e species. Other features of the mass spectrometric fragmentation of β-nitroamines are also discussed in the light of the spectra of the specific compounds discussed here.